PERLINDUNGAN HUKUM BAGI PENERIMA WASIAT TERHADAP NOTARIS YANG TIDAK MENDAFTARKAN DAN MELAPORKAN AKTA WASIAT - Sarah Patricia Rajagukguk; Siti Hajati Hoesin (The Juris, 2022)
One of the powers of a Notary is to be able to make a will as mandated in the UUJN, including making a will before witnesses as regulated in Article 939 paragraph (4) of the Civil Code and making a will without witnesses as regulated in Article 939 paragraph (2) of the Civil Code. A Notary in carrying out a legal action must always act carefully so that the Notary before making a deed must examine all relevant facts in his consideration based on the applicable laws and regulations. The making of a will by a Notary must pay attention to all the provisions regulated or determined in the provisions of the legislation governing the implementation of a will. So that in the future nothing happens that can harm the parties which can then also harm the Notary who made the will. This study focuses on discussing legal protection for will recipients against notaries who do not report a will. This study uses a normative juridical method with a statutory approach and an analytical approach. Legal protection for the beneficiary against a Notary who does not report the list of deeds, namely preventive legal protection and repressive legal protection. If in the making of the will, the requirements and elements have been determined as stipulated in the Civil Code and the Law on Notary Positions, then legal protection for the beneficiary will still exist and reporting is an administrative requirement that must be met.